Desenvolvimento de um roteiro para criação de vídeos como recursos audiovisuais no ensino de astronomia - Almeida, Ronaldo Pinheiro de (2021)
The Astronomy is one of the Science areas that stimulates the curiosity and the interest of the public in general. In a classroom we frequently face the need of solve the doubts about topics portrayed in movies and TV series, and most of these doubts about astronomy. The elementary subjects studied such as the Universe, its origin and Evolution, The Solar System and the terrestrial movements are the most interesting for the students, which actively participate in the classes and relate this information with the audiovisual ones that they have contact. In this sense, this research seeks to analyze the extend to which the influence of movies and TV series, so watched and debated in the social life of the young students, can harm or contribute to the comprehension of the concepts studied in Astronomy, producing understanding about the topics of this science area wrongly or well-founded. The research was developed with the elementary and high school students from the Reitor Edgar Santos State School in Feira de Santana, Bahia. In this work was produced as an educational result, which is configured as a script to assist in the production of vídeos made by students in order to create critical analysis of the information brought by the movies and TV series initially listed in this research. It was related the content of the Astronomy theories presented in the movies and TV series with their scientific theories, finding crucial points that approached or distanced them from the actual reality. The videos produced, on the other hand, cand be used in classroom as support material by teachers, be part of the material to participate in the structuring project “Production of Educational Videos (PROVE), performed by The Education Department of the State of Bahia and, depending on the choice of the students, be published on social networks as a vehicle of scientific dissemination.